Research Trends in Open Innovation and the Role of the University. - De-las-Heras-Rosas, Carlos Javier; Herrera-Ballesteros, Juan (MDPI, 2021)
Innovation is a key aspect for the sustainability and competitiveness of organisations, and of the economy in general. In recent years, Open Innovation (OI) has burst onto the scene as a more open approach, in which the sources and exchange of knowledge are extended beyond organisational borders. One of the main actors and providers of knowledge is the University. The literature related to OI and the University is very prolific, but at the same time dispersed. This paper aims to expand on the trend in research on OI and University. To do this, bibliometric techniques have been used to analyse a sample of 349 articles from journals indexed in the Web of Science (WoS) between 2005 and 2020. The results suggest that there is a high level of interest in research on this subject and that it is in full swing. The focus of the research is on topics such as collaboration, business–industry, R&D, networks, performance or knowledge-transfer. Emerging themes such as knowledge-spillover or absorptive-capacity appear, which are related to the research sensitivity on the true use of the knowledge generated. In recent years, there has been a trend towards research into entrepreneurship, key aspects of R&D such as strategy and cooperation, or education management. With regard to research related to University–Enterprise cooperation, the focus has been on SMEs, Helix models, entrepreneurship, or commercialisation. Finally, there are areas of research that require greater development related to family businesses and SMEs. This work sheds light on the state of the literature related to OI and University and is very useful for the orientation of future work in the field of research.
Keywords: Creatividad en la empresa; Innovaciones tecnológicas; Relaciones universidad-empresa; Transferencia de aprendizaje; Investigación científica y desarrollo; R&D; SciMAT; Open innovation; Knowledge transfer; Absorptive-capacity; University; Business; University–business